On Economic Policies of Unemployment in Europe - Pelagidis, Theodore (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1999)
This article deals with the unemployment problem in Europe. While the prevailing explanations sources of unemployment such as jobless growth, rigid labour markets and the process of globalization are rejected, it is argued that technological backwardness, slow growth and investment rates are responsible for the high European unemployment rate. A change in the mix of economic policy implemented in Europe is proposed in order to decelerate real interest rate, increase investments, GDP and employment.